S-scheme g-C3N4/PVA Heterojunction with Enhanced Photocatalytic Reduction of Aqueous Cr(VI) and Mechanism - Guo, Tianhong; Jiang, Yingxing; Luo, Yuanyuan; Liang, Xianhui; Zhao, Xinshan; Li, Jing (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2025)
Bulk g-C3N4 was synthesized using melamine as a precursor through thermal polymerization followed by high-temperature quenching. Subsequently, a g-C3N4/PVA heterojunction featuring evenly dispersed PVA on its surface was fabricated via in-situ hydrothermal synthesis. The impact of hydrothermal temperature and PVA concentration on the light absorption, bandgap energy, specific surface area, and charge carrier transport characteristics of g-C3N4/PVA were explored. Experimental findings indicate that PVA modification reduces nitrogen-vacancy defects in the g-C3N4/PVA heterojunction, thereby enhancing its visible-light photocatalytic activity compared to bulk g-C3N4. Specifically, g-C3N4/PVA-3 exhibits a 2.93-fold higher reaction rate for Cr(VI) photocatalytic reduction under visible light (0.017 min–1) than bulk g-C3N4 (0.0058 min–1), with a TOF of 0.0079 h–1. Electrochemical tests confirm that the enhanced activity arises from improved light-induced charge transfer and separation efficiency. Based on Mott-Schottky analysis and the identification of •OH and •O2– as reactive species, a mechanism for Cr(VI) reduction by S-scheme g-C3N4/PVA heterojunctions is proposed. This study presents an economically viable and efficient method for developing high-performance conjugated polymer-modified photocatalysts. Copyright © 2025 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).